0801 Sleep, Nightmares, and the Maintenance of Posttrauma Symptoms. (27th May 2020) - Meysing, A; Schulte, M; Youngren, W; Hamilton, N
Abstract: Introduction: Most individuals will experience at least one traumatic event in their lifetime. Although most individuals who experience a trauma will exhibit some posttrauma symptoms, only a small subset will experience long-lasting symptoms. In fact, most research suggests that posttrauma symptoms will gradually reduce over time. However, some individuals can exhibit posttrauma symptoms for an extended period of time. Although research has demonstrated that poor overall sleep quality may explain why some people have trouble gradually recovering from posttrauma symptoms, research has yet to examine specific aspects of sleep that can impair the gradual remission of posttrauma symptoms. This study examined how individual facets of sleep quality (such as nightmares and sleep duration) impact posttrauma symptoms over time. Methods: 944 college students completed an online survey battery that included measures of traumatic experiences, time since trauma (TST), posttrauma symptoms, sleep quality, and the presence of nightmares. Regression analyses were used to examine the interaction of sleep quality sub-facets and time since trauma on posttrauma nightmares (PNMs). Results: Out of 944 participants, 637 (67%) reported at least one trauma. Of those students, time since trauma (TST) and all other sleep variables significantly predicted posttrauma symptoms ( p < 0.05). However, the only significant interaction was nightmares and TST ( p < 0.01) where individuals who experienced PNMs had significantly ( p < 0.01) higher posttrauma symptom intercept (48.19) than individuals who did not experience PNMs (31.19). Furthermore, individuals who experienced PNMs demonstrated statistically significant flatter slopes than those without nightmares ( p < 0.01). Conclusion: The results reveal that time since trauma predicts a decrease in posttrauma symptoms, whereas nightmares impede this symptom reduction. Interestingly, the interaction finding suggests that nightmares play a critical role in initial symptom expression and recovery. These results demonstrate the importance of identifying and treating nightmares immediately following a trauma. Support: "none"